Fabrication of BiVO4/Bi12O15Cl6 heterojunction photocatalyst with enhanced photocatalytic performance under visible light. (24th May 2019) - Yan, Xu; Wu, Ziyang; Yang, Peipei; Fu, Yongmei; Ma, Wei; Zhao, Yong; Liu, Biao; Mao, Yanli; Shen, Hao; Jia, Lijun
Abstract: In this paper, BiVO4 /Bi12 O15 Cl6 was prepared by combination of ion exchange process and hydrothermal method. The photocatalytic performance of the as-prepared photocatalyst was systematically investigated via the photodegradation of tetracycline (TC) under visible light irradiation. The BiVO4 /Bi12 O15 Cl6 composites showed much higher photocatalytic efficiency than that of BiVO4 and Bi12 O15 Cl6 . The increased photocatalytic performance is attributed to the formation of heterojunction between BiVO4 and Bi12 O15 Cl6, which results in the effective charges separation and visible light absorption. Significantly, hydroxy radical (·OH) and superoxide radical · O 2 − were confirmed to be the dominant reactive species. Additionally, a direct Z-scheme mechanism was proposed on the basis of photoelectrochemical measurement and bang gap analyses.